Molecular markers and molecular basis of plant type related traits in maize - Zhao, Xinghua; Wang, Changbiao; Liu, Jiang; Han, Bin; Huang, Jinling (Frontiers in Genetics, 2024)
Maize, belonging to the Poaceae family and the Zea L. genus, stands as an excellent food crop. The plant type has a significant impact on crop growth, photosynthesis, lodging resistance, planting density, and final yield. In this study, 160 maize inbred lines were selected as experimental materials to conduct molecular markers research on maize plant type traits through the measurement of plant type-related traits, population structure, and genome-wide association analysis. The phenotypic data revealed differences in plant type-related traits among maize inbred lines grown in the Xinzhou and Jinzhong regions. The frequency distribution of plant height, ear height, spindle length of tassel, and first-order branch number of tassel traits in the 160 maize inbred lines previously studied generally conformed to a normal distribution. We identified 42,240 high-quality single nucleotide polymorphisms (SNPs) using the Affymetrix Axiom chip. The 160 maize inbred lines were categorized into six subgroups, each exhibiting an average gene diversity of 0.356 and an average polymorphism information content of 0.245. We identified 9, 23, 18, 8 and 32 loci that were significantly associated with first-order branch number of tassel, spindle length of tassel, ear height, plant height, and ear height/plant height ratio, respectively. At the same time, 6, 22, 14, 2, and 37 genes were identified as significantly associated with first-order branch number of tassel, spindle length of tassel, ear height, plant height, and ear height/plant height ratio, respectively. This study comprehensively delved into the genetic information of maize plant type-related traits, offering valuable genetic resources and a solid theoretical foundation for the breeding of novel maize varieties with optimized plant types.